2010
DOI: 10.1002/ddr.20406
|View full text |Cite
|
Sign up to set email alerts
|

Applying in silico tools to the discovery of novel CXCR4 inhibitors

Abstract: The process of HIV entry begins with the binding of the viral envelope glycoprotein gp120 to both the CD4 receptor and one of the CXCR4 or CCR5 chemokine co-receptors. There is currently considerable interest in developing novel ligands that can bind to these co-receptors and hence block virus-cell fusion. This article reviews the use of different in silico structure-based and ligand-based virtual screening (VS) tools for the discovery of potential HIV entry inhibitors for the CXCR4 receptor. More specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
(149 reference statements)
0
5
0
Order By: Relevance
“…Therefore, we must take this into account when analyzing our results, which show shape-matching scoring functions performing the poorest (AUC values for shape-matching scoring functions approximately random), since we used the isothiourea ligand in the structure as a unique representative shape-matching query. Recent studies have shown that using a consensus query, which can average the essential features of several known high-affinity scaffold families to take into account multiple binding subsite shapes, can highly improve shape-matching VS performance. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we must take this into account when analyzing our results, which show shape-matching scoring functions performing the poorest (AUC values for shape-matching scoring functions approximately random), since we used the isothiourea ligand in the structure as a unique representative shape-matching query. Recent studies have shown that using a consensus query, which can average the essential features of several known high-affinity scaffold families to take into account multiple binding subsite shapes, can highly improve shape-matching VS performance. ,, …”
Section: Resultsmentioning
confidence: 99%
“…For example, by including receptor backbone flexibility, it is possible to consolidate all the mutation data pertaining to the binding of the cyclam compounds [14]. Techniques that deal with "difficult targets", that is to say targets with multiple binding sites or multiple binding modes, have recently appeared in order to improve the screening performance, such as consensus shape screening [59][60][61].…”
Section: Discussionmentioning
confidence: 99%
“…For example, for CXCR4 inhibitors, Wong et al [226] and Pettersson et al [238] have reported binding-mode analyses for bicyclam, monocyclam, and noncyclam compounds [239]. Both agree that none of the dockings into CXCR4 can explain all mutant results by a direct ligandreceptor interaction.…”
Section: Case Study: Gpcr Drug Designmentioning
confidence: 99%
“…Hence, other potentially active compounds may be missed. Perez-Nueno et al [92][93][94][95] proposed a spherical harmonic (SH) consensus shape-matching algorithm to help solve this problem. In this approach, the shape of a consensus (or average) pseudomolecule is calculated from the SH representation of each active.…”
Section: Shape Matchingmentioning
confidence: 99%
See 1 more Smart Citation